Studying the loading impact of silane grafted Fe2O3 nanoparticles on mechanical characteristics of epoxy matrix - Hamdy M. Naguib; Mona A. Ahmed; Z.L. Abo-Shanab (Egyptian Journal of Petroleum)
This study investigates the loading impact of iron oxide (IO) and silane treated iron oxide (SIO) nanoparticles on thermal, mechanical and morphological behavior of epoxy matrix. Both IO and SIO nanoparticles were loaded with 1, 3 and 5 wt% from the total weight of epoxy matrix. The morphology of IO, and SIO epoxy nanocomposites are investigated by TEM. FTIR spectra are successfully able to confirm the good chemical interaction between SIO nanoparticles and epoxy matrix. Thermal resistance of epoxy IO, and SIO nanocomposites is studied by TGA. The mechanical properties of prepared nanocomposites including storage modulus, tan δ, stress-strain curves and toughness are studied using DMA at temperature range 25 °C–100 °C. The results approved that loading 3 wt% of SIO nanoparticles improved the morphological, thermal resistance and mechanical characteristics of epoxy matrix. Keywords: Iron oxide nanoparicles, Epoxy nanocomposites, Modulus, Toughness, Thermal stability